Matrine inhibits the adhesion and migration of BCG823 gastric cancer cells by affecting the structure and function of the vasodilator-stimulated phosphoprotein (VASP) - Zhang Jing-wei; Su Ke; Shi Wen-tao; Wang Ying; Hu Peng-chao; Wang Yang; Wei Lei; Xiang Jin; Yang Fang (Acta Pharmacologica Sinica, 2016)
Aim: Vasodilator-stimulated phosphoprotein (VASP) expression is upregulated in human cancers and correlates with more invasive advanced tumor stages. The aim of this study was to elucidate the mechanisms by which matrine, an alkaloid derived from Sophora species plants, acted on the VASP protein in human gastric cancer cells in vitro. Methods: VASP was expressed and purified. Intrinsic fluorescence spectroscopy was used to study the binding of matrine to VASP. CD spectroscopy was used to examine the changes in the VASP protein secondary structure. Human gastric carcinoma cell line BGC823 was tested. Scratch wound and cell adhesion assays were used to detect the cell migration and adhesion, respectively. Real-time PCR and Western blotting assays were used to measure mRNA and protein expression of VASP. Results: In the fluorescence assay, the dissociation constant for binding of matrine to VASP protein was 0.86 mmol/L, thus the direct binding between the two molecules was weak. However, matrine (50 μg/mL) caused obvious change in the secondary structure of VASP protein shown in CD spectrum. Treatments of BGC823 cells with matrine (50 μg/mL) significantly inhibited the cell migration and adhesion. The alkaloid changed the subcellular distribution of VASP and formation of actin stress fibers in BGC823 cells. The alkaloid caused small but statistically significant decreases in VASP protein expression and phosphorylation, but had no significant effect on VASP mRNA expression. Conclusion: Matrine modulates the structure, subcellular distribution, expression and phosphorylation of VASP in human gastric cancer cells, thus inhibiting the cancer cell adhesion and migration.